Editorial - Martí Domínguez (Mètode Science Studies Journal: Annual Review)
When the coronavirus pandemic broke out five years ago, one of the lessons we seemed to have learned was the importance of science and good science communication. In 2025, however, we are facing a resurgence of anti-science discourses in various fields: antivaccine movements, climate change denialism or the withdrawal of the United States from the World Health Organisation are some concerning examples.